Clinical characteristics associated with peripartum maternal bloodstream infection - Gao, Xiao-Li; Li, Yang; Hou, Su-Juan; Fan, Wen-Jun; Fang, Ling-Yi; Ni, Shi-Jun; Yan, Ye; Li, Jie; Han, Cha (Frontiers in Microbiology, 2024)
ObjectiveBloodstream infection (BSI) during the peripartum period is a major cause of maternal morbidity and mortality. However, data on maternal BSI during hospitalization for delivery are limited. This study aimed to investigate the incidence, clinical characteristics, risk factors, microbiological features, and antibiotic resistance patterns of maternal peripartum BSI, with a focus on understanding the role of premature rupture of membranes (PROM), fever, and other risk factors in its development.MethodsWe investigated the clinical characteristics associated with maternal BSI during the peripartum period. This study included febrile women with blood cultures obtained during hospitalization for delivery. We analyzed the clinical characteristics, pathogenic microorganisms, antibiotic resistance, and maternal and neonatal outcomes of these patients. Participants were divided into BSI (n = 85) and non-BSI (n = 361) groups.ResultsSpontaneous rupture of membranes, PROM, PROM >24 h before labor, vaginal examinations >5 times, and cesarean sections during labor were more common in the BSI group. Escherichia coli (51.8%; 44/85) was the predominant causative pathogen, followed by Enterococcus faecalis (7.1%, 6/85). Approximately 31.2% of E. coli were resistant to levofloxacin, and 38.6% were extended-spectrum β-lactamase-producing bacteria. The BSI group had higher rates of maternal sepsis and Apgar scores ≤ 7 at 1 min than the non-BSI group. Furthermore, PROM, fever ≥38.9°C (102°F), and fever within 24 h after delivery were risk factors for postpartum BSI in the adjusted analysis.ConclusionMaternal BSI is a potentially life-threatening disease associated with PROM and the timing and severity of fever. Early identification and surveillance of pathogen composition and antimicrobial resistance can help prevent adverse outcomes.